Structure peculiarities and properties of magnesium oxide layers formed by a hybrid ion-plasma discharge system - Duriagina, Z.A.; Pidkova, V.Ya.; Olshevska, S.O. (Functional Materials, 2013)
The structure and properties of magnesium oxide layers formed by a hybrid ion-plasma discharge system were investigated. The layers consist of the MgO phase which possesses a high degree of polycrystallinity. Grains are formed by the island mechanism with their subsequent joining in clusters. The dielectric layers of magnesium oxide are uniformly distributed over the substrate surface. The average values of grains diameter and surface roughness that are 82.353 and 35.628 nm, respectively, were found.